Resveratrol Alleviates Dextran Sulfate Sodium-Induced Acute Ulcerative Colitis in Mice by Mediating PI3K/Akt/VEGFA Pathway - Fang Zhu; Jujia Zheng; Fang Xu; Yiyuan Xi; Jun Chen; Xiangwei Xu (Frontiers in Pharmacology, 2021)
Ulcerative colitis (UC) is a chronic inflammatory disease that affects the colon, and its incidence is on the rise worldwide. Resveratrol (RSV), a polyphenolic compound, was recently indicated to exert anti-inflammatory effects on UC. Consequently, the current study was conducted to investigate the mechanism of RSV on alleviating UC in mice by mediating intestinal microflora homeostasis. First, potential targets that RSV may regulate UC were screened using the TCMSP database. Next, mice were treated differently, specifically subjected to sham-operation and dextran sulfate sodium (DSS) induction, and then treated or untreated with RSV. Disease Activity Index (DAI) and Hematoxylin-Eosin (HE) staining were employed to analyze the pathological changes of mice colon. In addition, the expression patterns of inflammatory factors in spleen tissues were detected using ELISA, while the protein expression patterns of phosphoinositide 3-kinase (PI3K), protein kinase B (Akt), and vascular endothelial growth factor A (VEGFA) in colon tissues were determined by means of immunohistochemistry (IHC) and Western blot analysis. Moreover, changes in intestinal flora and metabolite diversity in UC were analyzed by metabonomics. It was found that RSV played inhibitory roles in the PI3K/Akt pathway in mice. Meanwhile, the administration of RSV induced downregulated the expressions of TNF-α, IFN-γ, IL-1β, IL-6, and IL-4. The six floras of Haemophilus and Veillonella were significantly enriched in UC, while Clostridium, Roseburia, Akkermansia, and Parabacteroides were found to be enriched in control samples. Lastly, it was noted that Akkermansia could regulate the intestinal flora structure of UC mice through triacylglycerol biosynthesis, glycerol phosphate shuttle, cardiolipin biosynthesis, and other metabolic pathways to improve UC in mice. Altogether, our findings indicate that RSV suppressed the activation of the PI3K/Akt pathway and reduced the VEGFA gene expression to alleviate UC in mice.